Squeezing in a spin chain with site-dependent periodic and long-range interactions - Civitarese, Enrique Osvaldo (2010)
Numerical and analytical results for the squeezing factor, ζ^2, in a pseudo-spin s-1/2 chain. The open chain is composed by N two-level atoms with site-dependent interactions. The time evolution of the squeezing factor is studied, as well as its dependence on the number of atoms and on the interactions. It is found that long-range interactions may optimize the degree of spin squeezing.